An investigation of EFL learners’ foreign language anxiety in English language classroom in Afghanistan - Ziaurahman, Zia (2016)
The present study was conducted in order to investigate English as a foreign language (EFL) learners’ foreign language anxiety (FLA) in classroom activities in Afghanistan. Previous studies conducted on FLA have found that FLA affects learners’ language learning and achievements. This study aims to investigate the learners’ FLA which they experience during classroom activities and to determine if there are any differences in terms of these learners’ levels of FLA based on their gender. It also determines the reasons causing this anxiety among learners and suggests some coping strategies to help language teachers and learners minimize learners’ FLA. The participants of the study were composed of 115 first year English major undergraduates from English Language Department of Nangarhar University. The data was collected via questionnaire, Foreign Language Classroom Anxiety Scale (FLCAS), and semi-structured interviews. The study found that most of the Afghan EFL learners experienced high level of FLA and they mostly suffered from fear of negative evaluation (FNE) in their English language classroom. It was also found that female learners experienced more FLA compared to their male counterparts. Situations such as presentation, speaking in front of the English teacher or speaking in front of the class, and answering teacher questions, were found to be the most anxiety-provoking activities for these learners. Similarly, the respondents pointed out 11 reactions of FLA they exhibited in the language classroom activities which may greatly help language teachers identify anxious learners in the language classroom and help them in effective reduction of their FLA. The findings of this study are expected to be vital for classroom implications at tertiary level education in Afghanistan and for other similar educational and cultural contexts.